Analysis of socio-demographic factors affecting the management options for emesis gravidarum in pregnant women - Uliyatul Laili; Nur Zuwariah (Alma Ata University Press, 2022)
Background: Management of emesis in pregnancy depends on the severity of the symptoms felt by the pregnant woman. Treatment for emesis gravidarum can be carried out in several ways: pharmacological treatment which is the use of medical drugs, non-pharmacological treatment such as avoiding the consumption of coconut milk or fat-containing food, and frequent eating of small portion of food. In addition, the management of emesis gravidarum can also be done using a complementary treatment with acupressure, aromatherapy, and other methods. Currently, the type of management chosen by most health workers and accepted by pregnant women are pharmacological and non-pharmacological treatments. Recently, health workers have begun to develop and apply the use of complementary therapies in overcoming emesis gravidarum in pregnant women. Objectives: This study aims to analyze the characteristics of pregnant women that influence the choice of emesis gravidarum management.Methods: This was a cross sectional quantitative study. The research was conducted at the Independent Midwife Practice (PBM) Nanik, Sidoarjo. The population in this study were women in the 1st trimester of pregnancy. 43 respondents were taken as sample by using purposive sampling. The independent variables in this study were factors that influence the mother, such as age, occupation, education, parity, and knowledge. Meanwhile, the dependent variable was the emesis gravidarum therapy chosen (pharmacological, non-pharmacological and complementary therapies). The data were collected directly using questionnaires. Results: The results show that most of the respondents (67%) were those aged 21-35 years, 58% was primiparous mothers, 58% had secondary education, 51% was housewives, while 47% had good knowledge level about emesis gravidarum management. The bivariate analysis using chi square showed that education, occupation and knowledge had an effect on the choice of therapy for emesis gravidarum with p value < 0.05. Conclusions: Education, occupation, and knowledge were factors related to the choice of management for nausea and vomiting in pregnant women. Therefore, cooperation and the right decision making were necessary in determining the therapy for emesis gravidarum.